APPLICATION OF BIFURCATION THEORY TO CURRENT MODE CONTROLLED PARALLEL-CONNECTED BOOST DC-DC CONVERTERS - Isgenderov, Islam (Universiti Teknologi Petronas, 2006)
This project is to design a circuit which will guarantee stable operation at switching frequencies, and any quasi-periodic or chaotic operation is regarded as being undesirable and should be avoided. This project focuses in particular on the application of bifurcation theory to parallel-input / parallel-output two-module current-programmed DC-DC converters. Besides, this project describes the operation of Current Mode Controlled Parallel-Connected Boost DC-DC Converters and basically defines chaos, bifurcation and quasi-periodic distortion of the circuit by varying the reference current and comparing it with inductor output current. Within specific ranges of reference current the circuit operates without any distortion. The design includes the simulation of any bifurcation within the intended operation range by using PSpice, Multisim and EWB software. The inductor current output waveforms obtained and compared at different levels of reference currents. There are few ways to improve the output waveforms such as connecting freewheeling diode with parallel to inductor, using combination of triple input/triple output Current Mode Controlled converter or just using parallel input/series output configuration. Parallel-input / paralleloutput are the most common configuration that can be used in current mode control DC-DC converters. Simulation and calculation results shows that capacitor voltage ripple factor reduced from 30% to 3%(actual) and output current ripple from 20% to 3%. Improvement in this type of converter will open up new applications in datacommunication, telecommunication, power-supply in PC and inside the notebook, industrial automation and so forth. The core of the project work focuses on simulating the entire process and later building the prototype.